Impact of Alcohol Use Disorder Treatment on Clinical Outcomes Among Patients With Cirrhosis. Issue 6 (22nd May 2020) - Rogal, Shari; Youk, Ada; Zhang, Hongwei; Gellad, Walid F.; Fine, Michael J.; Good, Chester B.; Chartier, Maggie; DiMartini, Andrea; Morgan, Timothy; Bataller, Ramon; Kraemer, Kevin L.
Abstract : Background and Aims: Despite the significant medical and economic consequences of coexisting alcohol use disorder (AUD) in patients with cirrhosis, little is known about AUD treatment patterns and their impact on clinical outcomes in this population. We aimed to characterize the use of and outcomes associated with AUD treatment in patients with cirrhosis. Approach and Results: This retrospective cohort study included Veterans with cirrhosis who received Veterans Health Administration care and had an index diagnosis of AUD between 2011 and 2015. We assessed the baseline factors associated with AUD treatment (pharmacotherapy or behavioral therapy) and clinical outcomes for 180 days following the first AUD diagnosis code within the study time frame. Among 93, 612 Veterans with cirrhosis, we identified 35, 682 with AUD, after excluding 2, 671 who had prior diagnoses of AUD and recent treatment. Over 180 days following the index diagnosis of AUD, 5, 088 (14%) received AUD treatment, including 4, 461 (12%) who received behavioral therapy alone, 159 (0.4%) who received pharmacotherapy alone, and 468 (1%) who received both behavioral therapy and pharmacotherapy. In adjusted analyses, behavioral and/or pharmacotherapy‐based AUD treatment was associated with a significant reduction in incident hepatic decompensation (6.5% vs. 11.6%, adjusted odds ratio [AOR], 0.63; 95% confidence interval [CI], 0.52, 0.76), a nonsignificant decrease in short‐term all‐cause mortality (2.6% vs. 3.9%, AOR, 0.79; 95% CI, 0.57, 1.08), and a significant decrease in long‐term all‐cause mortality (51% vs. 58%, AOR, 0.87; 95% CI, 0.80, 0.96). Conclusions: Most Veterans with cirrhosis and coexisting AUD did not receive behavioral therapy or pharmacotherapy treatment for AUD over a 6‐month follow‐up. The reductions in hepatic decompensation and mortality suggest that future studies should focus on delivering evidence‐based AUD treatments to patients with coexisting AUD and cirrhosis.